Bilateral deficit magnitude increases with velocity during a half-squat exercise. Issue 11 (3rd June 2022) - Padulo, Johnny; Kuvačić, Goran; Ardigò, Luca Paolo; Dhahbi, Wissem; Esposito, Fabio; Samozino, Pierre; Cè, Emiliano
ABSTRACT: Movement velocity has been viewed as one of the bilateral deficit (BLD) determinants. This research tested the velocity effect on BLD during a half-squat exercise. The role of muscle excitation in BLD was also assessed. BLD amplitude was assessed in 12 male soccer players while performing a half-squat exercise with incremental load. During the exercise's pushing phase, the average force and velocity were measured in bilateral and unilateral conditions to provide the bilateral index (BI) at each interpolated velocity. The vastus lateralis and medialis excitation was assessed during the exercise by calculating the surface electromyography signal root mean square (sEMGRMS ). The BI for sEMGRMS (sEMG BI) was calculated. The theoretical maximum force (F0 ) and velocity (v0 ) were also determined. F0 was +43 (28)% in bilateral compared with unilateral conditions ( p < 0.001), whereas v0 was similar in both conditions ( p = 0.386). The BI magnitude rose with the increase in velocity from −34 (7)% at 50%v0 to −70 (17)% at 90%v0 ( p 0.03-<0.001), whereas no sEMG BI occurred ( p : 0.07-0.991 in both muscles). The study reported velocity-dependent changes in the BLD amplitude, with the largest BLD amplitudes occurring at the highest velocities. This behaviour could provide useful information for setting specific contraction velocities to exploit/limit the BLD amplitude as a possible training stimulus.